The village fund as a support tool in spatial planning activities: a case study of Poland - Feltynowski, Marcin (European Spatial Research and Policy, 2019)
With respect to space, local authorities may deploy diverse instruments designed to promote the engagement of local communities in the spatial planning and decision-making process. The Village (Polish: Sołecki) Fund, established for rural and urban-rural communes, is one of the ways for achieving this goal. Resources from the Village Fund may be used for, e.g. spatial planning, which is one of a commune’s own tasks. The activities related to the Village Fund have triggered studies focused on the units which run such funds and, on the amounts, earmarked for goals pertaining to spatial planning. On top of that, the spatial distribution of communes delivering such tasks has also been assessed. The analyses covered statistics as well as budget queries in communes which allocated funds for activities connected with spatial planning.